2017
DOI: 10.15666/aeer/1504_16971713
|View full text |Cite
|
Sign up to set email alerts
|

Does the Altitude Affect the Stability of Montane Forests? A Study in the Kahuzi-Biega National Park (Democratic Republic of the Congo)

Abstract: To understand the functioning of montane forests, this study was conducted in the highlands of the Kahuzi-Biega National Park in the Democratic Republic of the Congo. The relationship between the altitude and the floristic stability of woody layers and regeneration capability of canopy species after many years of disturbance was studied. Ten 1-ha plots were established from 1935m to 2760m a.s.l. In each plot we inventoried the trees ≥10cm of diameter at breast height (DBH), separating a canopy layer (10% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Some studies found that the relationship between tree species richness (for species with at least 10 cm of diameter at breast height) and elevation is unimodal, displaying a peak around 1000 m asl (Pierlot 1966;Doumenge 1998;Bhattarai and Vetaas 2006;Lee et al 2013), while others reported that tree species richness declines monotonically with increasing elevation (Stevens 1992;Zhao et al 2004;Kraft et al 2011;Zhu et al 2015). Most of these studies were performed in the temperate zone and few data are available on elevational gradients in tropical Africa (Pierlot 1966;Imani et al 2016;Cirimwami et al 2017). In the East African Mountains, when considering wide elevational gradients, patterns of tree species richness tend to present a maximum in the lower elevations of montane forests (Pierlot 1966;Doumenge 1998;Schmitt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that the relationship between tree species richness (for species with at least 10 cm of diameter at breast height) and elevation is unimodal, displaying a peak around 1000 m asl (Pierlot 1966;Doumenge 1998;Bhattarai and Vetaas 2006;Lee et al 2013), while others reported that tree species richness declines monotonically with increasing elevation (Stevens 1992;Zhao et al 2004;Kraft et al 2011;Zhu et al 2015). Most of these studies were performed in the temperate zone and few data are available on elevational gradients in tropical Africa (Pierlot 1966;Imani et al 2016;Cirimwami et al 2017). In the East African Mountains, when considering wide elevational gradients, patterns of tree species richness tend to present a maximum in the lower elevations of montane forests (Pierlot 1966;Doumenge 1998;Schmitt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between species richness and elevation has been shown to be a function of the vegetation lifeform studied (Zhao et al 2004;Grytnes et al 2006;Gairola et al 2008;Akhtar and Bergmeier 2015;Zhang et al 2016), variation of plant species richness in tropical mountain forests has been mainly studied focusing on trees with dbh ≥ 10 cm (Pierlot 1966;Hsieh et al 1998;Imani et al 2016;Cirimwami et al 2017;Gonmadje et al 2017) albeit the fact that the floristic richness of tropical forests is highly related to other lifeforms such as shrubs, lianas and herbaceous species (Gentry 1988;Bussmann 2001;Tchouto et al 2006). Along large gradients, shrubs' species richness tends to be negatively correlated with elevation, at least in the temperate zone (Akhtar and Bergmeier 2015).…”
Section: Introductionmentioning
confidence: 99%